2008
DOI: 10.1614/wt-07-017.1
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Metribuzin for The Control of Rigid Brome (Bromus rigidus) in No-Till Barley Crops of Southern Australia

Abstract: Field experiments were conducted at Warooka and Rudall on the Yorke and Eyre Peninsula of South Australia during 2004 and 2005 to investigate the effectiveness of metribuzin for the selective control of rigid brome in no-till sown barley. Metribuzin (135 to 203 g ai/ha) incorporated by sowing (IBS) was more effective in controlling rigid brome (> 67%) than the same herbicide dose applied POST. Although IBS metribuzin at the highest rate (270 g/ha) provided effective weed control (82 to 90%), it was more phytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Therefore, the best weed control with this herbicide was observed when it was applied at Z21-23 wheat stages. Kieloch et al (2006) indicated that pinoxaden can provide high levels of weed control even at late weed growth stage which was also supported by this study.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the best weed control with this herbicide was observed when it was applied at Z21-23 wheat stages. Kieloch et al (2006) indicated that pinoxaden can provide high levels of weed control even at late weed growth stage which was also supported by this study.…”
Section: Discussionsupporting
confidence: 86%
“…Metribuzin can also be used selectively to control Bromus spp. in barley crops, although high rates may cause crop damage on some soil types 36. Most importantly, weed numbers should be kept at a minimum through the use of integrated weed management options such as competitive crops and tools that deplete the soil weed seed bank, as resistance to some of the alternative herbicide control options has already been reported 16–18…”
Section: Discussionmentioning
confidence: 99%
“…Infestation of broad-spectrum weeds in dry-land farming is a major yield-reducing factor (up to 50%) in wheat [ 1 ]. Metribuzin [4-amino-6-(1,1-dimethylethy1)-3-(methylthio)-1,2,4-triazin-5-(4H)-one], a triazine herbicide (group C), is a versatile herbicide that controls a wide range of weeds in dry-land farming systems [ 1 , 2 ] and is registered for use in some wheat cultivars. However, most wheat cultivars lack selectivity to metribuzin due to narrow safety margins that result in crop damage.…”
Section: Introductionmentioning
confidence: 99%